The relationship among gender, interest in economic topics, media use, and the economic knowledge of students at vocational schools. (December 2019) - Förster, Manuel; Happ, Roland
The results of numerous studies indicate that male students achieve better results on economic knowledge tests than their female classmates. Although this phenomenon has been known for a long time, the gender-specific mechanisms of this gap have not been explored in depth. According to social and educational scientific theories and the current state of research, interest and media use could be related to gender. In this study, we administered a German adaption of the internationally accepted Test of Economic Literacy to explore the gender gap in the economic knowledge of 983 students from 62 classes at 7 vocational secondary schools and commercial vocational schools specializing in business and economics in Germany to determine whether it is significantly influenced by interest and media use. The results indicate that a considerable part of the gender gap can be clarified by effects of interest in economic topics and the use of media to research them. Implications for social and economic education are discussed.